Mapping upland rice potential in Casamance, Senegal: Field mission report - Rebolledo, María Camila; Audebert, A. (CGIAR FOCUS Climate Security, 2022)
Rice is one priority for Plan Senegal Emergent and the Senegalese Agricultural Acceleration Program (PRACAS) but irrigated rice investments are costly, not water efficient, and are concentrated in the north of Senegal. Where could rainfed rice (66% water saving) be an option for farming families in Casamance, for food security and drought resilience? This field visit and progress report presents the issue, methodology and stakeholder engagement in 2022. This upland rice activity proposes to develop crop model analytics (Target Population of Environments) to present evidence on upland rice potential/scaling pathways to farming organisations, research and extension services, food security and climate change decision bodies. The technical director of SODAGRI, the main field partner organisation and key stakeholder for Casamance agriculture programming will benefit from a PhD thesis thanks to complementary funding from the Agropolis foundation.